2018
DOI: 10.1186/s12974-018-1062-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the activation of pyroptotic and apoptotic pathways in RPE cells associated with NLRP3 inflammasome in the rodent eye

Abstract: BackgroundAge-related macular degeneration (AMD) is a devastating eye disease causing irreversible vision loss in the elderly. Retinal pigment epithelium (RPE), the primary cell type that is afflicted in AMD, undergoes programmed cell death in the late stages of the disease. However, the exact mechanisms for RPE degeneration in AMD are still unresolved. The prevailing theories consider that each cell death pathway works independently and without regulation of each other. Building upon our previous work in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…Inflammasome-mediated inflammation and cell death are widely accepted to be associated with both wet and dry forms of AMD 1,3,17,23,33,34,51 , with in vivo inhibition of inflammasome-activated pro-inflammatory cytokine IL-1β shown to greatly improve the survivability of the retina following photo-oxidative damage 14 . However, while much of the current literature has focused on investigating the role of inflammasome sensor receptor NLRP3 in propagating this damage, little work has been done on other components of inflammasome pathways, in particular on the role of pro-inflammatory-cleavage protease CASP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammasome-mediated inflammation and cell death are widely accepted to be associated with both wet and dry forms of AMD 1,3,17,23,33,34,51 , with in vivo inhibition of inflammasome-activated pro-inflammatory cytokine IL-1β shown to greatly improve the survivability of the retina following photo-oxidative damage 14 . However, while much of the current literature has focused on investigating the role of inflammasome sensor receptor NLRP3 in propagating this damage, little work has been done on other components of inflammasome pathways, in particular on the role of pro-inflammatory-cleavage protease CASP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to investigate if and how NLRP3 may be activated in AMD disease progression 21,[27][28][29][31][32][33][34][35][36] . However, to date studies using animal models have been focused on wet-AMD 21 , while those which investigate the role of NLRP3 in dry-AMD pathogenesis have been largely cell culture-based and focused on the RPE 19,21,22,27,28,31,32 .…”
mentioning
confidence: 99%
“…A recent trial suggested that dexamethasone reduces mortality in these patients [8] . Interestingly, in a refractory model of epilepsy, dexamethasone was able to abrogate neuroinflammatory signs and improve astrocyte function [9] ; in fact, this anti-inflammatory steroid has been proposed as an adjuvant therapy in cases of refractory epilepsy [10] . Therefore, we speculate that dexamethasone, beyond reducing mortality, could be useful for preventing or mitigating convulsive manifestations in COVID-19 patients.…”
Section: Commentarymentioning
confidence: 99%
“…In 2013, NLRP3 was first detected in RPE and drusen in AMD patients. Using human RPE cells, the study also provided the evidence that lysosomal destabilization triggered NLRP3-mediated inflammation [ 111 ]. However, markers of pyroptosis were not examined in this study.…”
Section: Novel Pcd Is Associated With Amdmentioning
confidence: 99%